ANALISIS SEMOTIKA LAGU MANGU DARI FOURTWNTY DALAM INTEPRETASI PERCINTAAN BEDA AGAMA - Adi Aminudien, Fakhri; Dewi Nuraini, Lisna (An-Nahdliyyah: Jurnal Studi Keislaman, 2025)
Songs or music are one form of musical communication because they contain meaning with symbols contained in the lyrics. This study aims to reveal the hidden meaning of the song "Mangu" by Fourtwnty feat Charita Utami, especially in the context of interfaith love. This study uses a qualitative approach with Ferdinand De Saussure's semiotic analysis method to distinguish between (signifier) ​​​​and signs (signified). which is emotionally complex, namely when starting from efforts to maintain relationships, to acceptance (surrender) due to differences in principles and directions of life. This study confirms that a musical work or song can function as a strong sign system to express meaning in conveying social and existential issues that are relevant to society.